Not only Distancing but also Uniting: Nurses' Experiences in Conflict management in a Culturally Diverse Hospital: A Qualitative Study - Yulia Kurniawati; Nurfika Asmaningrum; Dodi Wijaya; Kholid Rosyidi Muhammad Nur; Agustinha Soares (An Idea Health Journal, 2026)
Background: The increasingly diverse cultural environment in hospitals brings together nurses with varied cultural, linguistic, value-based, and educational backgrounds. This diversity increases the complexity of professional interactions and can lead to conflict, particularly due to differences in perception and communication. The present study explores nurses' experiences with conflict management in culturally diverse hospital settings. Methods: A qualitative phenomenological design was employed, with 12 purposively selected nurse participants. Data were collected through in-depth interviews and analyzed using thematic analysis. Result: Three main themes emerged: interpersonal differences, relational consequences, and adaptive conflict management. Interpersonal differences encompassed communication breakdowns as well as personal and sociocultural disparities. Relational consequences included both negative outcomes, such as disrupted nursing care and strained workplace relationships, and positive outcomes, such as the development of stronger relationships. Adaptive conflict management strategies involved self- regulation, dialogic communication, rational appraisal, and seeking support. Conclusion: The findings suggest that in culturally diverse contexts, conflict can serve not only as a source of tension but also as an opportunity to foster mutual understanding. Effective communication, emotional regulation, and organizational support are critical factors in constructively managing conflict.